Remittances and the Brain Drain: Evidence from Microdata for Sub-Saharan Africa - Julia Bredtmann; Fernanda Martínez Flores; Sebastian Otten (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
Research on the relationship between high-skilled migration and remittances has been limited by the lack of suitable microdata. We create a unique cross-country dataset by combining household surveys from five Sub-Saharan African countries that enables us to analyze the effect of migrants' education on their remittance behavior. Having comprehensive information on both ends of the migrant-origin household relationship and employing household fixed effects specifications that only use within-household variation for identification allows us to address the problem of unobserved heterogeneity across migrants' origin households. Our results reveal that migrants' education has no significant impact on the likelihood of sending remittances. Conditional on sending remittances, however, high-skilled migrants send significantly higher amounts of money to their households left behind. This effect holds for the sub-groups of internal migrants and migrants in non-OECD countries, while it vanishes for migrants in OECD destination countries once characteristics of the origin household are controlled for.
Keywords: F22; F24; O15; 330; migration; remittances; skill level; brain drain; Sub-Saharan Africa